2015
DOI: 10.3928/01477447-20150902-58
|View full text |Cite
|
Sign up to set email alerts
|

Complication Risk After Treatment of Intertrochanteric Hip Fractures in the Medicare Population

Abstract: The study evaluated the incidence of and complications associated with the use of an intramedullary nail vs open reduction and internal fixation (ORIF) with a sliding compression hip screw and plate in treating intertrochanteric fractures. The authors hypothesized that the biomechanically stronger and less invasive intramedullary nail would have superior results and fewer complications compared with ORIF. Patients followed for up to 1 year postoperatively were identified from the 5% nationwide sample of Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The study of Andrich and colleagues did not describe specific causes of death in the early period after pelvis fracture. Prior studies have examined cause of death primarily after hip fracture; although a minority of the early deaths are the result of postoperative complications such as delirium, pneumonia, acute cardiovascular events, and pulmonary embolism (Fig. , arrow a), the majority of deaths post‐hip fracture are from the same common comorbid conditions that are the causes of death in the broader older population (Fig.…”
Section: Early Post‐fracture Mortality: the Case Of Pelvis Fracturesmentioning
confidence: 99%
“…The study of Andrich and colleagues did not describe specific causes of death in the early period after pelvis fracture. Prior studies have examined cause of death primarily after hip fracture; although a minority of the early deaths are the result of postoperative complications such as delirium, pneumonia, acute cardiovascular events, and pulmonary embolism (Fig. , arrow a), the majority of deaths post‐hip fracture are from the same common comorbid conditions that are the causes of death in the broader older population (Fig.…”
Section: Early Post‐fracture Mortality: the Case Of Pelvis Fracturesmentioning
confidence: 99%
“…Studies have shown that early surgical intervention (within 24 h) can significantly reduce mortality [ 5 ]. Intramedullary fixation, with the advantages of withstanding the stress of the axis shift, good anti-fatigue performance, smaller incisions, and less damage to the local blood supply, is the most current treatment for IFs [ 2 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The movement time of partial weight-bearing patients in the hemiarthroplasty group was earlier than that in the PFNA group, and the Harris score of hip joints in the hemiarthroplasty group before discharge was also higher than that in the PFNA group. Therefore, for elderly patients with three or more intertrochanteric fractures, hemiarthroplasty can shorten the length of hospitalization and recovery time, and reduce the economic burden of such patients (23,24).…”
Section: Discussionmentioning
confidence: 99%